2020
DOI: 10.1055/s-0040-1721508
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Maneuver to Treat Refractory Atelectasis in Mechanically Ventilated Children

Abstract: We developed a novel airway clearance and lung recruitment maneuver for children with refractory unilateral atelectasis undergoing invasive mechanical ventilation. In this retrospective, single-center, proof of concept study, we describe the steps involved in this novel maneuver and evaluate its effectiveness in 15 patients through objective quantitation of changes in respiratory system compliance and in the degree of atelectasis assessed by a validated Modified Radiology Atelectasis Score. Compared with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(47 reference statements)
0
3
0
6
Order By: Relevance
“…We thank Gates et al for their interest in our recent publication 1 and appreciate the opportunity to respond to their comments. We admire their contributions to the field of pediatric airway clearance and are flattered by their engagement with our work.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…We thank Gates et al for their interest in our recent publication 1 and appreciate the opportunity to respond to their comments. We admire their contributions to the field of pediatric airway clearance and are flattered by their engagement with our work.…”
mentioning
confidence: 95%
“…5,6 We elect to perform tracheal suction during this derecruited state because, during the development of our maneuver, we found that the addition of this step yielded significantly more respiratory secretions than when suction was performed under standard conditions (with PEEP). As explained in our article, 1 we then carefully re-recruit the lung with manual inflation back to what will hopefully be a more compliant organ with balanced aeration.…”
mentioning
confidence: 99%
“…In the most recent edition of Journal of Pediatric Intensive Care , Martinez Herrada et al described a method of treating refractory atelectasis in a retrospective cohort of 15 mechanically ventilated children. 1 The authors reported that a combination of therapeutic techniques, in a standardized order of application, was associated with improvements in atelectasis scores and dynamic compliance compared with baseline measures.…”
mentioning
confidence: 99%
“…26 Em pacientes em VMI, geralmente envolve uma combinação de técnicas de desobstrução das vias aéreas, incluindo drenagem postural, hiperinsuflação manual (HM) intercaladas com vibrações torácicas (manuais ou mecânicas), percussões e sucção de secreções das vias aéreas. 9 Apesar das intervenções de fisioterapia respiratória incluírem diversas técnicas para o tratamento das atelectasias, 32 existem apenas quatro estudos [33][34][35][36] que citam métodos distintos de fisioterapia respiratória visando a resolução das atelectasias em pacientes pediátricos em VMI. Entretanto, nenhum deles trata-se de ensaios clínicos randomizados controlados ou padronizam as intervenções em protocolos.…”
Section: Tratamentounclassified
“…Apesar do conhecimento de que as complicações das atelectasias pulmonares interferem na morbimortalidade de pacientes em UTI e do aumento da efetividade e eficiência dos cuidados multiprofissionais quando da utilização de protocolos padronizados, não existe na literatura a descrição de cuidados multiprofissionais para a abordagem da atelectasia em pacientes pediátricos internados na UTIP. Assim como existem poucos estudos [33][34][35][36] incluindo a fisioterapia respiratória no tratamento das atelectasias em pediatria, torna-se importante a elaboração de um protocolo específico para esta situação clínica.…”
Section: Justificativaunclassified